INTERPRETIVE STUDY: THE MEANING OF RAHN GOLD ACCOUNTING PRACTICE IN THE PERSPECTIVE OF IMAM BUKHARI AND MUSLIM HADITH - Wahidahwati, Wahidahwati; Agustin, Yuliana; Handayani, Nur; Muhammad, Mazlina (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research aims to determine the accounting treatment of Sharia gold pawn products at Sharia Pegadaian, which is measured by the hadith perspective of Imam Al-Bukhari. Furthermore, those used as references include the story of Armor, rides or vehicles, and the story of the Ansar men. The research method used in this research is a case study approach. The case study focuses on the accounting treatment of gold Rahn transactions from the beginning of the contract to the end of the contract. The research results show that the contracts used in Sharia Pawnshops use Rahn contracts, qardh contracts, and ijarah contracts. However, in practice, several things are not under Imam Al-Bukhari's hadith, namely loans for qardh financing, the determination of administrative costs based on the size of the loan, the classification of ijarah discount rates as a percentage, and the combination of qardh and ijarah contracts. The practices following Imam Al-Bukhari's hadith are the ijarah fee system, full payment, and auction. It is recommended that in qardh financing, the customer (rahin) be given a loan of more than 95% of the value of the gold at that time. The costs incurred by the customer must calculate Sharia pawnshop administration costs. Ijarah discounts should not be measured as a percentage, and they must be measured in nominal terms to avoid speculation. Furthermore, customers must receive justice if they borrow some funds so that they do not use two contracts in one transaction.